2014
DOI: 10.1371/journal.pone.0087323
|View full text |Cite
|
Sign up to set email alerts
|

Reevesioside A, a Cardenolide Glycoside, Induces Anticancer Activity against Human Hormone-Refractory Prostate Cancers through Suppression of c-myc Expression and Induction of G1 Arrest of the Cell Cycle

Abstract: In the past decade, there has been a profound increase in the number of studies revealing that cardenolide glycosides display inhibitory activity on the growth of human cancer cells. The use of potential cardenolide glycosides may be a worthwhile approach in anticancer research. Reevesioside A, a cardenolide glycoside isolated from the root of Reevesia formosana, displayed potent anti-proliferative activity against human hormone-refractory prostate cancers. A good correlation (r2 = 0.98) between the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…The steroid may then be transported to the nucleus and play a role in the regulation of protein transcription. Cardiac glycosides have also been shown to affect the downregulation of tumour necrosis factor (TNF)‐ α and, along with c‐Myc, the NF‐ κ B pathway that leads to cell cycle arrest . The inhibition of the Na + /K + ‐ATPase can also play a role in the downregulation of multiple drug‐resistant proteins that allow cancer cells to resist to chemotherapy …”
Section: Molecular Targets Of Caridiac Glycosides As Anticancer Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The steroid may then be transported to the nucleus and play a role in the regulation of protein transcription. Cardiac glycosides have also been shown to affect the downregulation of tumour necrosis factor (TNF)‐ α and, along with c‐Myc, the NF‐ κ B pathway that leads to cell cycle arrest . The inhibition of the Na + /K + ‐ATPase can also play a role in the downregulation of multiple drug‐resistant proteins that allow cancer cells to resist to chemotherapy …”
Section: Molecular Targets Of Caridiac Glycosides As Anticancer Agentsmentioning
confidence: 99%
“…Cardiac glycosides have also been shown to affect the downregulation of tumour necrosis factor (TNF)-a and, along with c-Myc, the NF-jB pathway that leads to cell cycle arrest. 59 The inhibition of the Na + /K + -ATPase can also play a role in the downregulation of multiple drug-resistant proteins that allow cancer cells to resist to chemotherapy. 60 The inhibition of cardiac glycosides creates the endocytosis of the Na + /K + -ATPase.…”
Section: Effects On Gene Expression and Other Pathwaysmentioning
confidence: 99%
“…c-Myc may collaborate with several growth factors and kinases in regulating cyclin D1 expression. Therefore, it is suggested that targeting c-Myc and cyclin D1 may be a good anticancer strategy [26, 28]. However, the role of c-Myc on cyclin D1 expression needs further clarification (please see below).…”
Section: Resultsmentioning
confidence: 99%
“…c-Myc may collaborate with several receptors of growth factors, Ras/Raf mitogen-activated protein kinases cascade and PI3K/Akt through coordination in regulating cyclin D1 expression [26, 28, 34]. To determine the functional roles of c-Myc and Akt, plasmid transfection was performed and the effects on protein levels were examined using Western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation